1975
DOI: 10.1128/aac.7.5.629
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Resistant Mechanisms in Pseudomonas aeruginosa : Binding of Penicillin to Pseudomonas aeruginosa KM 338

Abstract: A comparison of the binding of radioactive penicillin G to whole cells and the membrane fraction derived from Pseudomonas aeruginosa KM 338 was made. This organism has intrinsic resistance to penicillin. The binding to the membrane fraction which catalyzed peptidoglycan synthesis followed saturation type kinetics and saturation was achieved at approximately 2 nmol of penicillin G per ml, whereas binding to the whole cells was entirely of the nonsaturation type. The binding of carbenicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The lipoteichoic acid inhibited either extracellular autolysin activity in culture supernatant or autolysis of whole cells in exponential phase of S. aureus. These results indicate that the prevention of penicillin-induced lysis of S. aureus by the lipoteichoic acid was brought about by the inhibition of autolytic activity of the organism.It has been well known that /3-lactam antibiotics are specifically and irreversibly bound to their target sites on the cytoplasmic membrane of Gram-positive1~4) and 3,5) where they inhibit cross-linking reaction in peptidoglycan synthesis6~11)The target sites are the penicillin binding proteins, transpeptidase and D-alanine carboxypeptidase12). Until recently, the bacteriolysis has been assumed to be induced by the binding of 8-lactam antibiotics to the penicillin binding proteins, indicating that the lysis was a consequence of the inhibition of cell wall biosynthesis2,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lipoteichoic acid inhibited either extracellular autolysin activity in culture supernatant or autolysis of whole cells in exponential phase of S. aureus. These results indicate that the prevention of penicillin-induced lysis of S. aureus by the lipoteichoic acid was brought about by the inhibition of autolytic activity of the organism.It has been well known that /3-lactam antibiotics are specifically and irreversibly bound to their target sites on the cytoplasmic membrane of Gram-positive1~4) and 3,5) where they inhibit cross-linking reaction in peptidoglycan synthesis6~11)The target sites are the penicillin binding proteins, transpeptidase and D-alanine carboxypeptidase12). Until recently, the bacteriolysis has been assumed to be induced by the binding of 8-lactam antibiotics to the penicillin binding proteins, indicating that the lysis was a consequence of the inhibition of cell wall biosynthesis2,13).…”
mentioning
confidence: 99%
“…It has been well known that /3-lactam antibiotics are specifically and irreversibly bound to their target sites on the cytoplasmic membrane of Gram-positive1~4) and Gram-negative bacteria2, 3,5) where they inhibit cross-linking reaction in peptidoglycan synthesis6~11)The target sites are the penicillin binding proteins, transpeptidase and D-alanine carboxypeptidase12). Until recently, the bacteriolysis has been assumed to be induced by the binding of 8-lactam antibiotics to the penicillin binding proteins, indicating that the lysis was a consequence of the inhibition of cell wall biosynthesis2,13).…”
mentioning
confidence: 99%
“…The organism used was Pseudomonas aeruginosa KM338, derived from ATCC 17653 ; this was the same strain as used in our previous study (Suginaka et al, 1975) of penicillin-resistant mechanisms. As estimated by a serial tube dilution method in Trypticase Soy Broth (BBL) with an inoculum of about lo4 bacteria ml-l, the minimal inhibitory concentrations of piperacillin, carbenicillin and benzylpenicillin were 12.5, 125 and 30000 pg ml-l, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It seems likely that this organism must lack some enzyme(s) of the cell wall biosynthetic pathway leading to cross-linking of peptidoglycan. It has been suggested that penicillin is specifically and irreversibly bound to transpeptidase in the cytoplasmic membrane of penicillin-susceptible (1,7,8) and relatively unsusceptible organisms, such as Pseudomonas.aeruginosa (10), and consequently inhibits the cross-linking reaction (1,7,9). The purpose behind this report was to determine the penicillin-binding ability of the isolated membrane from a strain of staphylococcal L-form, compared with that from its parent strain.…”
mentioning
confidence: 99%
“…The membrane fraction was obtained from the washed cell pellet by osmotic lysis, sonic treatment, and deoxyribonuclease digestion. The parent strain was grown in brain heart infusion broth (BBL) for 4.5 h (midlog phase), and the membrane fraction was prepared from the washed cells after lysis with cell wall lytic enzyme, ALE (11,12) Amersham/Searle, Buckinghamshire, England) as described previously (10).…”
mentioning
confidence: 99%